Behavior of ECAP processed copper electrodes in electrical discharge machining of AISI H13 steel. (2020) - Gopal, R.; Thangadurai, K.R.; Thirunavukkarasu, K.
Abstract: This work compares the behavior of unprocessed copper and equal channel angular pressed copper as electrode for spark machining in terms of rate of machining, rate of tool erosion and surface coarseness. The effect of the parameters such as current and pulse on time on the responses such as rate of machining, rate of tool erosion and surface coarseness were analyzed and compared. Among four electrodes, triple ECAP passed electrode gives superior quality in machining. It also reduces the surface coarseness around 50%. Triple ECAP passed electrode reduces the tool erosion by 55% compared to a bare electrode.